Metabolite profiling, identification and quantification of pectoralis major and serum from different chicken breeds - Tan, Cheng Keng (2022)
In Malaysia, local village chicken, known as “Ayam kampung”, is a premium chicken meat sold at a higher price than other chicken breeds. Food fraud involving the sale of colored broiler chicken as village chicken is motivated by a three to four-fold increase in profit due to their similar appearances and size. A previous study of chicken and beef products in Malaysia's local markets reported that approximately 78% of these products were associated with meat substitution and mislabelling. The objectives of this study are to distinguish four chicken breeds and further identify potential distinguishing metabolites corresponding to each chicken breed using gas chromatography-mass spectrometry (GC-MS) and nuclear magnetic resonance (NMR) spectroscopy with an untargeted metabolomics approach. Four types of chicken breeds were obtained from commercial farms, comprising of local village chicken, broiler chicken (Cobb), spent laying chicken (Dekalb), and colored broiler chicken (Hubbard). All pectoralis major and serum samples of four chicken breeds were analyzed using GC-MS and NMR. The multivariate analysis was applied through principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA) assessments for GC-MS and NMR results. For GC-MS, all four chicken breeds were successfully separated into three distinct groups, with 30 and 40 characteristic metabolites identified for the pectoralis major and serum, respectively. Similarly, for NMR, all four chicken breeds were separated into three main groups, with 14 and 14 characteristic metabolites identified for the pectoralis major and serum, respectively. Both pectoralis major and serum were characterized by an abundance of metabolites comprising amino acids (alanine, glutamic acid, glycine, threonine, serine), fatty acid (linoleic acid), nucleotides (inosine monophosphate, nicotinamide adenine dinucleotide), organic acids (lactic acid, succinic acid and 3-hydroxybutyric acid), peptide (anserine), sugars (allose and glucose), sugar alcohol (myo-inositol), and other compounds under both analytical platforms. From the multivariate analysis, local village chicken was successfully differentiated from other commercial breeds by pectoralis major and serum under GC-MS and NMR, respectively. The present GC-MS results for pectoralis major showed that local village chicken was not separated from colored broiler (Hubbard). In conclusion, the present results proved that an untargeted metabolomics approach coupled with GC-MS and NMR is suitable for differentiating different chicken breeds from commercial farms. The identified potential metabolites characterized for respective chicken breeds derived from multivariate analysis provide basic information on discriminating metabolites and references in chicken meat authentication for related regulatory authorities.